Orthogonal Discrimination among Functional Groups in Ullmann-Type C–O and C–N Couplings - Rovira, Mireia; Soler, Marta; Güell, Imma; Wang, Ming-Zheng; Gómez, Laura; Ribas, Xavi (Journal of organic chemistry, 2016)
The copper-catalyzed arylation of nucleophiles has been established as an efficient methodology for the formation of C–C and C–heteroatom bonds. Considering the advances during the last two decades, the ligand choice plays a key role in such transformations and can strongly influence the catalytic efficiency. The applicability of these Ullmann-type coupling reactions regarding the orthogonal selectivity of different functional groups constitutes a challenging subject for current synthetic strategies. Herein, we report a useful toolkit of Cu-based catalysts for the chemoselective arylation of a wide-range of nucleophiles in competitive reactions using aryl iodides and bromides. We show in this work that the arylation of all kinds of amides can be orthogonal to that of amines (aliphatic or aromatic) and phenol derivatives. This high chemoselectivity can be governed by the use of different ligands, yielding the desired coupling products under mild conditions. The selectivity trends are maintained for electronically biased iodobenzene and bromobenzene electrophiles. Radical clock experiments discard the occurrence of radical-based mechanisms.